Hamstring vs Peroneus Longus Tendon Autograft in Anterior Cruciate Ligament Reconstruction: A Comparative Study - Khadri M Khalid; Adarsh Vajrangi; Eswara Reddy; Nagesh Sherikar; Rakshith Chakravarthy Harish Yellappa; Ranganatha B Kurupati (Journal of Orthopedics and Joint Surgery)
Introduction: Anterior cruciate ligament (ACL) injury is one of the most common knee ligament injuries. There is much debate about the best treatment for this injury, and many studies have been conducted to compare different graft options. Hamstring (HT) autografts have withstood the test of time and are currently the most commonly used graft for ACL reconstruction (ACLR). However, there are also many alternative graft options that have been explored and are being used. In this article, we will explore whether the peroneus longus (PL) graft can be a comparable alternative to the HT graft. Materials and methods: We conducted a prospective randomized study involving 80 patients who underwent ACLR. These patients were divided into two equal groups randomly—the HT group and the peroneus longus tendon (PLT) group. To evaluate functional outcomes, we utilized the International Knee Documentation Committee (IKDC) score for the knee joint, while the American Orthopaedics Foot and Ankle Scoring System (AOFAS) was employed for assessing the ankle joint. To gauge donor site morbidity, we measured thigh circumference preoperatively and postoperatively. These measurements were taken at 1- and 2-year follow-up intervals. Results: A total of 80 patients were evaluated with a minimum follow-up of 2 years. In terms of clinical outcomes and knee stability, neither group displayed any discernible differences. The diameter of the PL graft was substantially bigger than the diameter of the HT. The PLT group did not appear to have any abnormal ankle joint function according to the assessment of AOFAS and ankle range of motion (ROM). The HT group showed a significant wasting of the quadriceps when compared to the PLT group. Conclusion: With regard to its strength, larger graft diameter, satisfactory ankle function, and prevention of potential complications of HT autograft obtained from the knee region, the current study demonstrated that PLT autograft might be considered a safe and practical autograft source for arthroscopic ACLR.